A TERAPIA COMPORTAMENTAL DIALÉTICA (DBT) NO TRATAMENTO DE TRANSTORNOS ALIMENTARES: UMA ANÁLISE QUALITATIVA A PARTIR DA GROUNDED THEORY (CIPEEX, 2026)
The present study seeks to analyze the application of Dialectical Behavior Therapy (DBT) in the treatment of Eating Disorders (EDs) from the perspective of Grounded Theory. Eating disorders are complex conditions that involve persistent alterations in eating behavior, significantly impacting both physical and psychosocial health. DBT, developed by Marsha Linehan, has proven effective not only for the treatment of Borderline Personality Disorder but also for other conditions marked by emotional dysregulation, such as EDs. The research investigates how the principles of DBT—particularly the skills of emotional regulation, mindfulness, distress tolerance, and interpersonal effectiveness—can be applied in the management of patients with anorexia nervosa, bulimia nervosa, and binge eating disorder. The study examined the effectiveness of DBT in comparison with other approaches, assessing its contribution to reducing relapses, strengthening emotional regulation, and improving patients’ quality of life.
Keywords: Terapia Comportamental Dialética; Transtornos Alimentares; Regulação Emocional; Grounded Theory